2014
DOI: 10.1155/2014/747282
|View full text |Cite
|
Sign up to set email alerts
|

Restauration Fonctionnelle du Rachis : Effet du Niveau Initial de Douleur sur Les Performances des Sujets Lombalgiques Chroniques

Abstract: Intensive care programs are very useful for the treatment of chronic low back pain; however, the initial pain intensity reported by patients may affect the degree of improvement following participation in such programs. The authors of this article aimed to determine whether an intensive spine functional restoration program would be as effective for individuals presenting with severe pain as those presenting with mild to moderate pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Similar conclusions were drawn by Binderup et al [13] as a result of research on the pain threshold in the lumbar spine, as well as by Żywień and Sipko [14] on the basis of algometer tests of women and men from the professional group of computer We have found that in terms of functional efficiency, men with back pain caused by degenerative changes are characterized by greater limitations in terms of activities related to care. Also, crossgender qualityoflife comparisons by Ogunlana et al [16] in 220 patients with nonspecific low back pain treated at a health center in southwestern Nigeria showed worse functional performance and quality of life in men. On the other hand, Czaja et al [17] found no relationship between the ODI results and the sex of patients treated for lumbosacral disc herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions were drawn by Binderup et al [13] as a result of research on the pain threshold in the lumbar spine, as well as by Żywień and Sipko [14] on the basis of algometer tests of women and men from the professional group of computer We have found that in terms of functional efficiency, men with back pain caused by degenerative changes are characterized by greater limitations in terms of activities related to care. Also, crossgender qualityoflife comparisons by Ogunlana et al [16] in 220 patients with nonspecific low back pain treated at a health center in southwestern Nigeria showed worse functional performance and quality of life in men. On the other hand, Czaja et al [17] found no relationship between the ODI results and the sex of patients treated for lumbosacral disc herniation.…”
Section: Discussionmentioning
confidence: 99%
“…Les facteurs influençant l'endurance musculaire chez le patient lombalgique sont encore mal connus. D'après Caby et al en France, l'intensité de la douleur influencerait les capacités d'endurance [36]. En effet, dans sa série la moyenne du test de Sorensen pour les patients avec une douleur modérée (EVA< 7/10) était de 65+/-47 sec et pour ceux avec une douleur intense (EVA > 7/10) était de 37+/-33 sec, avec une différence cependant non significative.…”
Section: Résultatsunclassified